Regional competitiveness and local government debt - Wojtasiak-Terech, Agnieszka (Konkurencyjność regionu a zadłużenie jednostek samorządu terytorialnego, 2019)
The goal of the research was to select measures of regional competitiveness and analyze if in the considered period changes in value of these measures were in line with changes in the debt level of different forms of municipalities (communes). The survey was conducted for the Lower Silesia region and the municipalities located there. Data covered the period 2005-2015. The main measure of regional competitiveness selected by the author was regional GDP per capita. The additional measures were: labour productivity, employment rate, average monthly salary and business density. The survey indicated that the value of communes debt in Lower Silesia increased, even if in some years for particular forms of communes the level of debt was decreasing. At the same time generally an increase of competitiveness measures in the region was observed. In most of the analyzed years the direction of changes in municipalities debt was the same as that of changes of regional competitiveness measures
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2019; vol. 63, nr 12, s. 152-164